2016
DOI: 10.1038/nn.4452
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally defined forebrain circuits regulate appetitive and aversive olfactory learning

Abstract: Postnatal and adult neurogenesis are region- and modality-specific, but the significance of developmentally distinct neuronal populations remains unclear. We demonstrate that chemogenetic inactivation of a subset of forebrain and olfactory neurons generated at birth disrupts responses to an aversive odor. In contrast, novel appetitive odor learning is sensitive to inactivation of adult born neurons, unveiling that developmentally defined sets of neurons may differentially participate in hedonic aspects of sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…In contrast, the number of P14-generated interneurons located in the MCL and sGCL was similar to that in the dGCL ( Figure S2). These data were consistent with previous studies (Lemasson et al, 2005;Muthusamy et al, 2017). To examine the developmental effect of Abl1 in the postnatal early-born OB interneuron, we knocked down the expression of Abl1 in newborn neurons from the SVZ at P0 by injecting lentivirus-bearing, interfering, small-hairpin RNA against the control (shCTL) or the Abl1 (shAbl1) and tur-boGFP (tGFP) into the lateral ventricles ( Figure 2A).…”
Section: Requirement Of Abl1 For Proper Localization Of Postnatal Earsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, the number of P14-generated interneurons located in the MCL and sGCL was similar to that in the dGCL ( Figure S2). These data were consistent with previous studies (Lemasson et al, 2005;Muthusamy et al, 2017). To examine the developmental effect of Abl1 in the postnatal early-born OB interneuron, we knocked down the expression of Abl1 in newborn neurons from the SVZ at P0 by injecting lentivirus-bearing, interfering, small-hairpin RNA against the control (shCTL) or the Abl1 (shAbl1) and tur-boGFP (tGFP) into the lateral ventricles ( Figure 2A).…”
Section: Requirement Of Abl1 For Proper Localization Of Postnatal Earsupporting
confidence: 89%
“…Previous studies demonstrated that postnatal early-and lateborn interneurons have different cell fates in OB circuits (Kao and Lee, 2010;Muthusamy et al, 2017;Osterhout et al, 2014). By the incorporation of 5-bromo-2 0 -deoxyuridin (BrdU) at P0 or P14, as a representative stage of late-born interneurons, we also found that P0-generated interneurons dominantly located into the mitral cell layer (MCL) and the sGCL.…”
Section: Requirement Of Abl1 For Proper Localization Of Postnatal Earmentioning
confidence: 75%
See 1 more Smart Citation
“…To test the odor responses of OB neurons under satiated and fasted states, different types of odorants were used. Isoamyl acetate and 2-heptanone were used as neutral odorants, peanut butter [24][25][26] and food odor were used as appetitive odorants, and 2,4,5-trimethylthiazole and peppermint oil [27] were used as aversive odorants. To confirm that the mice had a preference for the appetitive odorants and avoided the aversive odorants, we performed a preference/avoidance test ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…While the cellular and molecular bases for such distinct responses are not known, these results are in line with observations showing that adult-born neurons are more responsive to incoming odors than their older counterparts 4,37 and that these 2 populations of cells participate differently in the hedonic aspects of odor information processing. 41 How do these 2 forms of structural plasticity cooperate to optimize the response of the OB network to a constantly changing odor environment? Since spine relocation and synaptogenesis occur on different time scales, it is likely that these 2 forms of plasticity accommodate rapid and long-lasting changes in the odor environment, respectively.…”
Section: Different Forms Of Structural Plasticity Of Gcs In the Obmentioning
confidence: 99%